A phase III randomized, open-label, non-inferiority clinical trial comparing liquid and lyophilized formulations of oral live attenuated human rotavirus vaccine (HRV) in Indian infants - Catherine Cohet; Brigitte Cheuvart; Leentje Moerman; Dan Bi; Adrian Caplanusi; Mallesh Kariyappa; Sanjay Lalwani; Monjori Mitra; Amita Sapru; Shruti Saha; P.V. Varughese; Rajeev Zachariah Kompithra; et al. (Taylor & Francis Group, 2021)
The human rotavirus vaccine (HRV; Rotarix, GSK) is available as liquid (Liq) and lyophilized (Lyo) formulations, but only Lyo HRV is licensed in India. In this phase III, randomized, open-label trial (NCT02141204), healthy Indian infants aged 6-10 weeks received 2 doses (1 month apart) of either Liq HRV or Lyo HRV. Non-inferiority of Liq HRV compared to Lyo HRV was assessed in terms of geometric mean concentrations (GMCs) of anti-RV immunoglobulin A (IgA), 1-month post-second dose (primary objective). Reactogenicity/safety were also evaluated. Seroconversion was defined as anti-RV IgA antibody concentration ≥20 units [U]/mL in initially seronegative infants (anti-RV IgA antibody concentration <20 U/mL) or ≥2-fold increase compared with pre-vaccination concentration in initially seropositive infants. Of the 451 enrolled infants, 381 (189 in Liq HRV and 192 in Lyo HRV group) were included in the per-protocol set. The GMC ratio (Liq HRV/Lyo HRV) was 0.93 (95% confidence interval [CI]: 0.65-1.34), with the lower limit of the 95% CI reaching ≥0.5, the pre-specified statistical margin for non-inferiority. In the Liq HRV and Lyo HRV groups, 42.9% and 44.3% (baseline) and 71.4% and 73.4% (1-month post-second dose) of infants had anti-RV IgA antibody concentration ≥20 U/mL, and overall seroconversion rates were 54.5% and 50.0%. Incidences of solicited and unsolicited adverse events were similar between groups and no vaccine-related serious adverse events were reported. Liq HRV was non-inferior to Lyo HRV in terms of antibody GMCs and showed similar reactogenicity/safety profiles, supporting the use of Liq HRV in Indian infants.